ADMISSÃO POR PRIMEIRO EMPREGO E REEMPREGO NO MERCADO FORMAL BRASILEIRO E CEARENSE: ANÁLISE COMPARATIVA DA REMUNERAÇÃO ENTRE 2010 E 2020/Admission for first employment and reemployment in the formal market in Brazil and Ceará: comparative analysis of remuneration in 2010 and 2020 - Alves de Sousa, Ana Leticia; Nunes de Queiroz, Silvana (Informe GEPEC, 2024)
O presente estudo tem como objetivo geral analisar a presença de diferença salarial entre trabalhadores admitidos por primeiro emprego e por reemprego no Brasil e no Ceará, nos anos de 2010 e 2020. O tipo de pesquisa é descrititvo-explicativa, utilizando o método dedutivo a partir da utilização do procedimento comparativo, além do método quantitativo para apresentar e explicar as diferenças encontradas. Os dados foram coletados a partir da Relação Anual de Informações Sociais (RAIS), do Ministério do Trabalho e do Emprego (MTE). Os principais resultados apontam que tanto para o Brasil quanto para o Ceará há discriminação de sexo, e os maiores níveis de contratação estão concentrados nos empregados que possuem o ensino médio completo, e na faixa etária de 18 a 24 anos ocupam o maior contingente de admitidos por primeiro emprego, enquanto de 30 a 39 anos por reemprego. Além disso, a maioria das admissões por primeiro emprego são regidas pela CLT e é o grupo que mais sofre demissões tanto no Brasil quanto no Ceará, sendo a diferença salarial maior no país. Abstract: The present study has the general objective of analyzing the presence of a wage difference between workers admitted for the first job and for re-employment in Brazil and Ceará, in the years 2010 and 2020. The type of research is descriptive-explanatory, using the deductive method from the use of the comparative procedure, in addition to the quantitative method to present and explain the differences found. Data were collected from the Annual Social Information List (RAIS), from the Ministry of Labor and Employment (MTE). The main results indicate that both for Brazil and for Ceará there is gender discrimination, and the highest levels of hiring are concentrated in employees who have completed high school, and in the age group of 18 to 24 years old occupy the largest contingent of admitted for first job, while from 30 to 39 years old for re-employment. In addition, most first admissions are governed by the CLT and those who sufferthe most dismissals are those hired for the first job both in Brazil and in Ceará, with the wage difference being greater in the country.